Design of an ultra-durable silicon-based battery anode material with exceptional high-temperature cycling stability. (August 2016) - Park, Hyungmin; Choi, Sinho; Lee, Sung-Jun; Cho, Yoon-Gyo; Hwang, Gaeun; Song, Hyun-Kon; Choi, Nam-Soon; Park, Soojin
Abstract: Nanostructured silicon is a promising candidate material for practical use in energy storage devices. However, high temperature operation remains a significant challenge because of severe electrochemical side reactions. Here, we show the design of ultra-durable silicon made by introducing dual coating layers on the silicon surface, allowing stable operation at high temperature. The double layers, which consist of amorphous metal titanate and carbon, provide several advantages including: (i) suppression of volume expansion during Li + insertion; (ii) creation of a stable solid-electrolyte−interface layer; and (iii) preservation of original Si morphology over 600 cycles at high temperature. The resulting silicon-based anode exhibits a reversible capacity of 990 mA h g −1 after 500 cycles at 25 °C and 1300 mA h g −1 after 600 cycles at 60 °C with a rate of 1 C. Graphical abstract: A new class of Si-based materials is fabricated by synergistic coupling of amorphous ABOx and carbon coating layers onto Si particles. In this system, ABOx stabilizes the SEI layers, while carbon acts as an electrical conducting material. The resulting Si-based anodes exhibit high specific capacities (1667 mA h g −1 (25 °C) and 2021 mA h g −1 (60 °C) at 1 C rate) and highly stable cycling performances (capacity retention of 60% after 500 cycles at 25 °C and 64% after 600 cycles at 60 °C). Highlights: We synthesized a new class of Si-based anode materials by synergistic coupling of amorphous ABOx and carbon coating. ABOx stabilizes the solid-electrolyte-interphase layers, while carbon acts as an electrical conducting material. Si-based anodes show exceptional high-temperature cycling stability with a high specific capacity of 1300 mA h g −1 after 600 cycles.